Identifying Dostors' Problems In Breaking Bad News: An Initial Step In Developing Recommendations For The Curriculum - Miko Ferine; Gandes Retno Rahayu; Mora Claramita (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2017)
Background: The skill of breaking bad news is listed in the 2012 Indonesia’s Doctor Competency Standards so that this becomes one of the skills that must be mastered by all doctors in Indonesia. The curriculum of breaking bad news is much developed in western cultural background. The curriculum may not necessarily be well developed in Indonesia because the communication process is strongly influenced by culture. Therefore, the exploration of the problems faced by the practitioner in delivering bad news in the context of local cultural needs to be done as a first step to develop the right educational curriculum and training.Objective: This study aimed to identify problems of the practicing doctors in delivering bad news to patients or their families in the context of local culture (Banyumas).Methods: This study was a qualitative research with a phenomenological approach. The method used was in-depth interviews to the practicing doctors with experience in delivering bad news selected from various educational backgrounds, sex, and age.Results: This study indicated that the doctors had difficulty in breaking bad news. It was known from the attitude of the doctors who tended to avoid by giving the task to others, to cover the actual condition of the patient or just delivering the bad news to the family. The causes identified were the lack of knowledge and skills, the lack of ability to control emotions, the lack of confidence, the anxiety on the patient’s response, the knowledge gap between doctors and patients, and the limitations of space and time.Conclusion: The main problem of the practicing doctors in delivering bad news was the lack of knowledge and skills. Therefore, it is necessary to develop a training curriculum on breaking bad news adequately for basic and advanced medical education.